Traumatic Rupture of Posterior Tibial Tendon Following Closed Supination-Adduction Ankle Fracture: A Case Report. Issue 3 (July 2016) - Krishna, Sathya Vamsi; Pilar, Anoop; Pai, Sudhir N.; Issac, Thomas
Abstract : Case: A 25-year-old man with no known comorbidities presented with pain and swelling of the left ankle following a twisting injury that had occurred during a road traffic accident. On examination, a 1 × 1-cm abrasion was noted on the medial malleolus and tenderness was noted over the medial and lateral malleoli. A radiograph of the left ankle revealed a fracture of the medial malleolus and an infrasyndesmotic avulsion fracture of the lateral malleolus (a supination-adduction injury). Immediate surgery was performed for the treatment of the medial malleolar fracture. On exploration, the posterior tibial tendon was found to be severed and frayed 2 cm proximal to the medial malleolar fracture. The medial malleolus was fixed with 2 parallel malleolar screws. The ruptured tendon was explored proximally, and the ends were debrided and repaired. Conclusion: At 1 year of follow-up, the ankle had good union and function of the tendon was restored. Posterior tibial tendon ruptures, although rare, should be suspected in cases of closed ankle fracture, irrespective of the mechanism of injury.